STUDI KELAYAKAN PENGEMBANGAN DAN INVESTASI PERUMAHAN ALFARISI GRAND RESIDENCE TAMBUN SELATAN, KABUPATEN BEKASI - Ajeng Dwifebrianti; Priyendiswara Agustina Bella (Jurusan Arsitektur dan Perencanaan, 2022)
Housing is one of the main human needs as a place to live, so the need for housing is increasing from time to time, especially in developing areas. Bekasi Regency is one of the buffer cities that has also experienced regional development, especially in the road infrastructure sector, one of which is the construction of a new toll road, namely the Cibitung-Cililitan Toll Road. The development of toll road infrastructure facilitates community mobility, especially in the Bekasi Regency area. Seeing this potential, a housing development is planned on land located on Jalan Raya Jejalen-Jabir, Sumberjaya Village, South Tambun District, Bekasi Regency. The land is close to the construction of a new toll road with the closest toll gate access to the Gabus Toll Gate approximately 3.5 kilometers from the land. The development trend of the residential property market around the land also provides opportunities with market demand for lower-middle class housing properties in the land location area. The main objective of this feasibility study is to determine the potential and constraints that exist both physically, legally, market opportunities, and financial development. The feasibility analysis is carried out based on the analysis of the physical, legal, market, and financial aspects of the investment using qualitative methods and the discounted cash flow method for investment feasibility analysis. The results of this study are in the form of feasibility status and several recommendations for the development of land to be developed into residential land. Keywords: Development; Feasibility Study; Investment; Residential Abstrak Rumah menjadi salah satu kebutuhan utama manusia sebagai tempat tinggal, sehingga kebutuhan akan tempat tinggal semakin meningkat dari waktu ke waktu khususnya pada kawasan yang sedang berkembang. Kabupaten Bekasi merupakan salah satu kota penyangga yang turut mengalami perkembangan kawasan terutama pada sektor infrastruktur jalan, salah satunya pembangunan jalan tol baru yaitu Jalan Tol Cibitung-Cililitan. Pembangunan infrastruktur jalan tol mempermudah mobilitas masyarakat khususnya pada kawasan Kabupaten Bekasi. Melihat potensi tersebut maka direncanakan pengembangan perumahan pada lahan yang berlokasi di Jalan Raya Jejalen-Jabir, Desa Sumberjaya, Kecamatan Tambun Selatan, Kabupaten Bekasi. Lahan tersebut berada dekat dengan pembangunan jalan tol baru dengan akses pintu tol terdekat Pintu Tol Gabus berjarak kurang lebih 3,5 kilometer dari lahan. Tren pengembangan pasar properti perumahan di sekitar lahan juga memberikan peluang dengan adanya permintaan pasar terhadap properti rumah kelas menengah-bawah di kawasan lokasi lahan. Tujuan utama studi kelayakan ini adalah untuk mengetahui potensi dan kendala yang ada baik secara fisik, legalitas, peluang pasar, dan finansial pengembangan. Analisa kelayakan dilakukan berdasarkan analisis pada aspek fisik, legalitas, pasar, dan finansial investasi dengan metode kualitatif dan metode discounted cash flow untuk analisis kelayakan investasi. Hasil studi ini berupa status kelayakan dan beberapa rekomendasi terhadap perkembangan lahan yang akan dikembangkan menjadi lahan perumahan.